“Right to the City” and insurgent practices: insights from two decades of the Right to the City law in Brazil Clarissa - Freitas, Sampaio; Miraftab, Faranak (AESOP, 2016)
In this paper we focus on the experience of Brazil with the Right to the City movement, whose claims were institutionalized in 2001 through the legal mechanism “Statute of the City”, and on the federal campaign for municipalities to develop democratic master plans. Following more than a decade of struggle since the 1980s, Brazilian citizens have created programs to secure inclusive cities where poor inhabitants can assert and enjoy their right to be in the cities and in their neighborhoods. Using studies of insurgent urban movements and emergent scholarship on insurgent planning, we reflect on the Brazilian experience to highlight the limitations of a rights-based approach to achieving inclusive cities and neighborhoods. We also examine the ways in which legislative protection for disadvantaged urban inhabitants can coexist with, and sometimes reinforce, marketbased dispossession of the urban poor. Even when insurgent movements succeed in formalizing citizens’ rights to the city whereby institutions provide programs, laws, regulations, and mechanisms for protecting and asserting citizens’ rights (as the Brazilian legislation has done), such formal recognitions will fall short in securing inclusive planning and will sometimes embolden market practices that exclude the poor from urban development. Our perspective challenges the often commonly used argument that elitist developments persist despite the adoption of a progressive rights discourse. We argue that, in some instances, it is precisely a more progressive perspective that has allowed the implementation of exclusionary practices. This claim is pursued by exploring the struggles of informal settlements residents in Bom Jardim, a peripheral neighborhood of Fortaleza.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south